A new species of Deltaspis Audinet-Serville (Coleoptera: Cerambycidae: Cerambycinae) from Mexico - Eya, Bryan K. (Zootaxa, 2017)
As currently defined, the genus Deltaspis Audinet-Serville, 1834, contains 16 species ranging in distribution from the southwestern United States to eastern Mexico. However, the generic distinction between Deltaspis and its closely allied genera, such as Crossidius LeConte, 1851 and Muscidora Thomson, 1864, is in need of clarification. According to Audinet-Serville, Deltaspis is so named due to its distinctive triangular scutellum (i.e., Δετα, delta, ασπιζ écusson), which is actually a commonly shared character of all these genera. Members of the tribe Trachyderini Dupont (1836), which includes the above genera, also have mandibles with an emarginate-truncate apex with the edge chisel-like or bifid. This modification of mouthpart appears to be for consumption of pollen and/or petals from composite flowers visited by the adult beetles (Krenn et al., 2005; Beierl & Barchet-Beierl, 1999). Other genera from this tribe with this modification of mandibles from North America, and mostly from Mexico, include: Chemsakiella Monné, 2006, Giesbertia Chemsak & Linsley, 1984, Hoegea Bates, 1885, Neocrossidius Chemsak, 1959, Paroxoplus Chemsak, 1959, Plionoma Casey, 1912, Schizax LeConte, 1873, and Tylosis LeConte, 1850. The remainder of Trachyderini genera have unmodified or simple mandibles with apex acute.